The Effect of Problem-Based Learning Model Assisted By Learning Animation Video on Student Learning Outcomes - Khoiriyah, Siti; Mayasari, Novi; Khoirotunnisa’, Anis Umi (Journal of Mathematics Education and Science, 2025)
The purpose of this study is to determine the effect of a problem-based learning model supported by educational animation videos on students' learning outcomes. The research approach used is quantitative with a quasi-experimental design. The population of this study consists of seventh-grade students, with class VII-C serving as the control group and class VII-D as the experimental group, each consisting of 31 students. The results of the study indicate that the problem-based learning model assisted by educational animation videos yields better results than direct learning, as evidenced by the average scores increasing from 62.081 to 84.613 in the experimental class, while the control class improved from 63.048 to 79.452. Hypothesis testing using the t-test also supports this finding, with a t-table value of 2.00 at a 5% significance level, while the calculated t-value is 2.669. Therefore, since the calculated t-value is greater than the t-table value (2.669 > 2.00), it can be concluded that there is an effect of the problem-based learning model assisted by educational animation videos on students' learning outcomes.